Analisis Pendidikan Karakter Peserta Didik melalui Penerapan Kultur Sekolah di SD Negeri Karangasem 1 Surakarta - Binti Khoiriyah; Anggit Grahito Wicaksono, Oka Irmade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Currently, Indonesia is facing a character education issue that needs attention. As time progresses, character education in students is weakening. Therefore, educational institutions have a crucial role in addressing this issue. One strategy implemented by SD Negeri Karangasem 1 Surakarta in developing this character education is through the implementation of a school culture program. The existence of this school culture program can help instill positive habits in students. By habituating these positive habits, the formation of character education will be easier to instill in students. This research method uses a qualitative with a descriptive approach. Data collection techniques used are observation, documentation, and interviews. To test the validity of the data in this study, triangulation techniques were used. Data analysis techniques used are data collection, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the school culture program can shape religious, nationalist, independent, mutual cooperation, and integrity character education.